Review: Influence of alloy addition and spinel coatings on Cr-based metallic interconnects of solid oxide fuel cells - Hassan, M.A. (Elsevier Ltd, 2020)
Solid oxide fuel cell (SOFC) is the modern eco-friendly technology of fuel cell power generation system. It generates electricity from a redox chemical reaction without producing hazardous gases. It consists of anode, cathode and electrolyte. It is operated in the form of stack connected by interconnects to boost-up power output. The recent development of low-temperature (600 Â°Câ800 Â°C) brings an opportunity to use metallic interconnects over ceramics. Cr-based metallic interconnects are one of the prominent metallic interconnects. They offer chemical inertness, thermal stability, compatible coefficient of thermal expansion and highly dense structure. However, the Cr-migration towards the cathode side is the major problem in them which adversely affect the SOFCs performance. Therefore a good oxidation resistance without sacrificing electrical conductivity is required. To resolve this issue, several alloying elements and spinel coatings have experimented. These spinel coatings are the thin solid films of Mn, Co, Cu and rare earth metals. This review concluded that the MnâCo based spinal coating showed excellent performance in reducing the Cr-migration in specially designed expensive Crofer 22 APU interconnect. However, the emerging low-cost ferritic interconnects also show their best results with CuâFe based spinel coating. Among them, the SUS-430 interconnect shows the equivalent performance of Crofer 22 APU interconnect after surface treatment and appropriate CuâFe based spinel coating. Therefore, it can replace the Crofer 22 APU interconnect on a cost basis. Â© 2020 Hydrogen Energy Publications LLC